2016
DOI: 10.1002/mop.30307
|View full text |Cite
|
Sign up to set email alerts
|

All electronic propagation loss measurement and link budget analysis for 350 GHz communication link

Abstract: In this work, we measure the propagation losses for estimating the performance of a communication link in the frequency band of 350 GHz. The losses are measured by having a transmitter and receiver at varying distances upto 8.5 m. Due to limited ability to move the transmitter and receiver, reflection methods are employed. Using this simple method, we show the presence of water absorption lines in the spectra at 380 and 448 GHz. We also study the data‐rate enhancement using dielectric lenses. Finally, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Propagation loss measurements for estimating the performance of a communication link in the 350 GHz frequency band were presented in [124], where a VNA based system was used with 26 dBi gain co-polarized horn antennas at both the TX and RX. The presence of water absorption lines in the spectra at 380 GHz and 448 GHz was very evident.…”
Section: Channel Sounding and Channel Properties Above 100 Ghzmentioning
confidence: 99%
See 1 more Smart Citation
“…Propagation loss measurements for estimating the performance of a communication link in the 350 GHz frequency band were presented in [124], where a VNA based system was used with 26 dBi gain co-polarized horn antennas at both the TX and RX. The presence of water absorption lines in the spectra at 380 GHz and 448 GHz was very evident.…”
Section: Channel Sounding and Channel Properties Above 100 Ghzmentioning
confidence: 99%
“…The presence of water absorption lines in the spectra at 380 GHz and 448 GHz was very evident. Data rates of 1 Gbps for a 8.5 m link and 100 Gbps for a 1 m T-R separation distances were shown to be possible via wireless communication links at 350 GHz [124]. Channel and propagation measurements at 300 GHz were presented in [125], [126], where a VNA based channel system with 26 dBi gain horn antennas at both TX and RX was used to analyze the channel characteristics from 300-310 GHz with an IF frequency bandwidth of 10 kHz.…”
Section: Channel Sounding and Channel Properties Above 100 Ghzmentioning
confidence: 99%
“…In [ 36 ], the channel was characterized at 350 GHz based on ray-tracing simulations where the high-gain antennas influence the transmission conditions and position of the transmitter (Tx) for optimal signal coverage; and the achievable data rate was presented for different propagation conditions in generic indoor scenarios. At the same frequency of 350 GHz, Bhardwaj et al [ 37 ] measured the propagation loss using a VNA-based system to estimate the communication link performance and stated that the wireless communication link at 350 GHz can support 1 Gpbs and 100 Gbps along 8.5 m and 1 m links, respectively. In [ 32 ] it was reported that 1.3 Tbps and 0.9 Tbps throughput can be achieved over 0.1 m links within a 140 GHz bandwidth of the 260–400 GHz band for LoS and NLoS scenarios, respectively.…”
Section: Overview Of Radio Wave Propagation For 6g Systemsmentioning
confidence: 99%
“…The communication between passengers and rails as well as intra-wagon scenarios are characterized using ultra-wideband channel sounding and ray tracing at 60-300 GHz frequency bands with 8 GHz of bandwidth [75]. The measured propagation losses of a communication link at 350 GHz frequency estimates the data rates of 1Gbps at 8.5 m and 100Gbps for 1 m distances [76]. Channel models and propagation measurements are presented at D-band (110-170 GHz) frequencies.…”
Section: Channel Modelling and Measurementsmentioning
confidence: 99%